EU Leadership in Energy and Environmental Governance
XVI, 229 p.
Keywords: This edited collection focuses on the impact of the changing global distribution of power on the EU's energy policy and ability to project its approach to energy-related issues abroad. It maps the EU's changing position on global energy, the impact of various factors on its energy policy, and its relations with Russia, China, the USA and Brazil.